9x+45=3(4x-3)

Simple and best practice solution for 9x+45=3(4x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+45=3(4x-3) equation:


Simplifying
9x + 45 = 3(4x + -3)

Reorder the terms:
45 + 9x = 3(4x + -3)

Reorder the terms:
45 + 9x = 3(-3 + 4x)
45 + 9x = (-3 * 3 + 4x * 3)
45 + 9x = (-9 + 12x)

Solving
45 + 9x = -9 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
45 + 9x + -12x = -9 + 12x + -12x

Combine like terms: 9x + -12x = -3x
45 + -3x = -9 + 12x + -12x

Combine like terms: 12x + -12x = 0
45 + -3x = -9 + 0
45 + -3x = -9

Add '-45' to each side of the equation.
45 + -45 + -3x = -9 + -45

Combine like terms: 45 + -45 = 0
0 + -3x = -9 + -45
-3x = -9 + -45

Combine like terms: -9 + -45 = -54
-3x = -54

Divide each side by '-3'.
x = 18

Simplifying
x = 18

See similar equations:

| 5(x-2)+10=5x-25 | | 150a-555= | | 8x+10y=210 | | 3v^3+4v^2+9v+12= | | 1a-46= | | 4=3c-17 | | 2(x-3)=-9 | | a+2a=.08 | | 15/x-2=9/x | | 7x+5=2(3x+12) | | l+4=-2 | | 7(x-2)=3x-2 | | 9-x+8=-6 | | 15=x+12 | | e+-43=-45 | | 4(b-5)+5b(8-6b)= | | 7x+3=2x+58 | | -16(t^2-361)=0 | | 0.3(3n-5)=0.4-0.2(n-7) | | (q-5)*2=10 | | 12xX=72 | | a-52=112 | | (q-8)*3=6 | | X^2=5x+8 | | c=15+4*9 | | c=15+4*8 | | c=15+4*7 | | x-10=70-7x | | (e+1)*5=10 | | c=15+4*50 | | 2(z+2)-5=7 | | X^2y+3xy+xy^2=0 |

Equations solver categories